The impacts of petroleum price fluctuations on income distribution across ethnic groups in Malaysia - Saari, M. Yusof; Dietzenbacher, Erik; Los, Bart (Elsevier, 2016)
Crude oil price hikes have compelled governments of developing countries to let domestic prices of energy increase. Fiscal priorities made it impossible to fully compensate the hikes by raising energy subsidies. This paper examines the potential impacts of a limited deregulation of the petroleum price on the income distribution in Malaysia, paying specific attention to differences in impacts on major ethnic groups. We introduce an extended social accounting matrix (SAM) model, which not only incorporates substitution possibilities among production inputs and consumption goods, but also allows for the exogenous determination of the price of intermediate inputs. The results of simulations indicate that distributional impacts of rising petroleum prices tend to be regressive, affecting poor people more severely than richer people. All ethnic groups experience income loss with the real incomes of Malay households (which are relatively poor, on average) more than the Chinese and Indian households (which are the generally richer).